2023
DOI: 10.25259/jnrp_338_2023
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative anemia in children undergoing elective neurosurgery: An analysis of incidence, risk factors, and outcomes

Shweta Naik,
Amruta Nirale,
Suparna Bharadwaj
et al.

Abstract: Objectives: Pediatric neurosurgeries carry a considerable risk of intraoperative bleeding and, subsequently, anemia in the post-operative period. Postoperative anemia is often multifactorial with several factors contributing to its occurrence. The present study aims to quantify the incidence of postoperative anemia, identify potential risk factors, and assess the impact of post-operative anemia on clinical outcomes in the pediatric neurosurgery population. Materials and Methods: This was a single-center and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A recent study in children undergoing neurosurgery demonstrated higher ASA grade, lower preoperative hemoglobin and lower intraoperative RBC transfusion to be associated with postoperative anemia. 24 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study in children undergoing neurosurgery demonstrated higher ASA grade, lower preoperative hemoglobin and lower intraoperative RBC transfusion to be associated with postoperative anemia. 24 …”
Section: Discussionmentioning
confidence: 99%